Simulating 3D crack propagation with XFEM to investigate failure mechanism in high strength concrete. Issue 1 (25th January 2021) - Patel, Rohan; Scheiden, Tim; Hüpgen, Markus; Rozanski, Corinna; Loehnert, Stefan; Oneschkow, Nadja
Abstract: High strength concrete compared to normal strength concrete has a denser micro‐structure, i.e. tight packaging or bonding between glued aggregates and cement paste, which increases strength and durability. The disproportionate ratio in ingredients of concrete, water to cement ratio and binding agents to form cement paste are subjected to self‐desiccation during the hydration process which leads to shrinkage, that has potential to form micro‐cracks and delamination within the ITZ (Interfacial Transition Zone), which ultimately causes deterioration in health of the structure. In order to investigate this phenomenon, a computational model to simulate the formation and propagation of cracks within the micro‐structure is developed. The geometrical model for the computation and simulation of the micro‐structure is extracted by means of computer tomography (CT) scans of concrete samples. The eXtended Finite Element Method (XFEM) in combination with level set techniques is employed to simulate discrete cracks and their advancement within the micro‐structure. The criterion for the crack propagation is obtained from a gradient enhanced damage model and once it is fulfilled, the crack geometry is updated using an advance algorithm for level sets.